Value add palm oil through cross metathesis using 1-octene - Thangavel, Mythili; Chin, Sim Yee (2021)
Palm oil can be value added through cross-metathesis process with the purpose to convert it to the compounds with lower molecular weight and fatty acids having terminal double bonds which is used as a feedstock for polyol production. Metathesized triglycerides (mTAGs) are truncated versions of the natural oil feedstock with unique terminal unsaturation content.